ANALYSIS NEED OF FLIPBOOK ASSISTED E-MODULE DEVELOPMENT IN ENGLISH COURSES - Eva Yuni Rahmawati; Mira Gusniwati (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2022)
This research aims to analyze the need for teaching English courses in Mathematics Education Studi Program, namely e-modules assisted by flipbooks. The subjects in this research were lecturers in English courses and students who took English courses. Data collection techniques in this research used to interview and questionnaire techniques. Data analysis in this research consisted of, data reduction, data presentation, and drawing conclusions. The results of this research are lecturing and problem-based methods, students have difficulty in learning English material, student interest in learning English courses is still low, and teaching materials used textbooks, and PowerPoint. E-module or flipbook had never been used. The results of literature studies and field studies indicate that it is necessary to develop an e-module or a flipbook in English courses.